From solidarity to prosperity: Exploring the impact of Islamic Waqf on economic development: Insights from the Kuwaiti experience - Mustapha, Zaaba (International journal of economic perspectives, 2024)
The main objective of the study is to highlight the importance of utilizing the Islamic Waqf (Endowment) system by states in achieving the desired economic development goals. The study begins with the literature on waqf in Islam, in terms of its concept and some of its jurisprudential rulings, such as the four pillars of waqf. In the second part of the research, the fundamental concepts related to economic development were pointed out, in particular economic development’s objectives and its five dimensions. In the next section, we tried to link the variables of the study “Waqf and Economic development.” On the one hand, we showcased the effects of Waqf in achieving social welfare such as solidarity and social justice; and on the other hand, the effects on economic dynamics such as stimulating demand and promoting investment were brought to attention. Finally, the case of Awqaf (endowments) in the State of Kuwait was diagnosed, starting with a historical overview of awqafin Kuwait and the state’s endeavours to manage them. Afterwards, the contribution of awqaf in reaching the economic development’s goals was analysed. The research findings provide evidence that Kuwait has a successful experience in waqf system management as well as in making Islamic Waqf supporting the economic development. The market value of waqf assets in Kuwait amounted to 4.81 billion, and revenues from waqf investments amounted to 157.44 million in 2022. Kuwaiti awqaf support the economic activity of various sectors by allocating 11 diverse endowment funds, and the total market value of these contributions in 2022 was estimated at 1.93 billion.